Hubungan Hasil Belajar Mata Pelajaran Produktif terhadap Kesiapan Kerja Siswa Sekolah Menengah Kejuruan - Putri Mayang Sari; Hendri Hendri (Jurnal Pendidikan Teknik Elektro, 2023)
This study aims to analyze the relationship between Productive Subject Learning Outcomes and Job Readiness of Grade XI ITTL Students at SMK Negeri 1 West Sumatra. The method used in this research is correlational research using a correlational quantitative approach. The subjects of this study were class XI ITL students at SMK Negeri 1 West Sumatra, consisting of 36 students. Determination of respondents is done by selecting odd numbers of student attendance. So that in sampling each student is represented respectively. Data collection uses questionnaires and documentation, for the instrument score system using a Likert scale. Before being distributed to the main respondents of the study, the questionnaire was validated by an expert lecturer validator of the Department of Electrical Engineering and also conducted a trial stage of the instrument to determine the validity and reliability of the instrument through Class XI ITTL students in West Sumatra state vocational schools. The trial respondents were taken from outside the research sample in the same population, the number of trial respondents was 20 students. Data analysis techniques using Percentage and Product Moment. The results show that (1) The learning outcomes of productive subjects of ITL students at SMK Negeri 1 West Sumatra are categorized as low, this can be seen from the respondents who predominantly get grades with the title C. (2) The work readiness of ITL students at SMK Negeri 1 West Sumatra is categorized as high. (3) There is no significant relationship between the learning outcomes of productive subjects (X) and work readiness (Y) of TITL students at SMK Negeri West Sumatra. Because the significance value obtained is 0.023 <0.329, which means there is no relationship.